A New Quasi‐Solid Polymer Electrolyte for Next‐Generation Na–O2 Batteries: Unveiling the Potential of a Polyamide‐Polyether System - Mohamed Yahia; Marina Enterría; Cristina Pozo‐Gonzalo; Nagore Ortiz‐Vitoriano (Advanced Science)
Abstract A novel quasi‐solid polymer electrolyte (QSPE) composed of polyamide (PA) and polyethylene oxide (PEO), commercially known as Pebax1657, and combined with 1 M sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) in diethylene glycol dimethyl ether (diglyme, DEGDME), has been investigated for sodium–oxygen (Na–O2) batteries. Pebax1657 QSPE exhibits high ionic conductivity (6.57 × 10−4 S cm−1 at room temprerature ‐ RT), an oxidation onset potential of 4.69 V versus Na/Na⁺, and an enhanced Na⁺ transference number (tNa⁺ ≈ 0.40). Structural analysis (Raman spectroscopy, differential scanning calorimetry, X‐ray diffraction, small‐angle X‐ray scattering) confirms reduced PEO crystallinity and formation of orderly nanodomains, facilitating Na⁺ transport. Long‐term galvanostatic cycling in Na|Na symmetrical cells demonstrates stable overpotentials (≈80 mV) at 75 µA cm⁻2 for 210 h, outperforming conventional liquid electrolytes (≈110 h). Pebax1657 QSPE enables higher discharge capacities (2.60 mAh cm⁻2 at 75 µA cm⁻2; 2.11 mAh cm⁻2 at 150 µA cm⁻2) with lower overpotentials (≈0.2 V). It sustains 25 cycles at 75 µA cm⁻2 and 35 cycles at 150 µA cm⁻2 at 0.25 mAh cm⁻2, with a Coulombic Efficiency (CE) of 80–90%. Compared to the state of the art, Pebax1657 QSPE offers improved electrochemical stability, lower overpotentials, and better capacity retention. Its sustainability and versatility make it a strong candidate for Na–O2 batteries and other energy storage applications.